Elicitation of Highly Pathogenic Avian Influenza H5N1 M2e and HA2-Specific Humoral and Cell-Mediated Immune Response in Chicken Following Immunization With Recombinant M2e–HA2 Fusion Protein - Kalaiyarasu, Semmannan; Bhatia, Sandeep; Mishra, Niranjan; Senthil Kumar, Dhanapal; Kumar, Manoj; Sood, Richa; Rajukumar, Katherukamem; Ponnusamy, Boopathi; Desai, Dhruv; Singh, Vijendra Pal (Frontiers in Veterinary Science, 2021)
The study was aimed to elicit Highly Pathogenic Avian Influenza (HPAI) virus M2e and HA2 specific immunity in chicken to develop broad protective influenza vaccine against HPAI H5N1. Based on the analysis of Indian AIV H5N1 sequences, the conserved region of extra cellular domain of M2 protein (M2e) and HA2 were identified. Synthetic gene construct coding for M2e and two immunodominant HA2 conserved region was designed and synthesized after codon optimization. The fusion recombinant protein (~ 38 kDa) was expressed in prokaryotic system and characterized by western blotting with anti-His antibody and anti-AIV polyclonal chicken serum. The M2e-HA2 fusion protein was found to highly reactive with known AIV positive and negative chicken sera by ELISA. Two groups of SPF chickens were immunized (i/m) with M2e synthetic peptide and M2e-HA2 recombinant protein along with one control group with booster on 14th day and 28th day with the same dose and route. Pre-immunization sera and whole blood were collected on day 0 followed by 3, 7, 14, 21, 28 day and two week after 2nd booster (42 day). Lymphocyte proliferation assay by MTT method revealed that stimulation index (SI) was increased gradually from day 0 to 14 in immunized group (p<0.05) than control chicken. All the chicken TLRs mRNA expression were analyzed by RT-qPCR and found maximum upregulation in day 3 and 7 of M2e-HA2 group than M2e and control group. M2e-HA2 recombinant protein based indirect ELISA revealed that M2e-HA2 recombinant fusion protein has induced strong M2e and HA2-specific antibody responses from 7 days post primary immunization and then the titer gradually increased after booster dose. Similarly, M2e peptide ELISA revealed that M2e-HA2 recombinant fusion protein elicited M2e specific antibody from day-14 onwards. In contrast, no antibody response was detected in the chicken immunized with synthetic peptide M2e alone or control group. Findings of this study will be very useful in future development of universal influenza vaccine targeting M2e and HA2.